Compact, hydrophilic, lanthanide-binding tags for paramagnetic NMR spectroscopy1. Issue 4 (16th April 2015) - Lee, M. D.; Loh, C.-T.; Shin, J.; Chhabra, S.; Dennis, M. L.; Otting, G.; Swarbrick, J. D.; Graham, B.
<x xml:space="preserve">Abstract</x> The design, synthesis and evaluation of four novel lanthanide-binding tags for paramagnetic NMR spectroscopy are reported.